Air transport services in remote regions - Svein Bråthen (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
The need for public support. The existing programs for public support have been made with reference to the need for essential air transport services for providing local communities with lifeline transport services. However, the criteria for giving public support (via the programs in USA, Canada and Europe) allows for quite wide interpretation of the terms remote regions and lifeline services. In some places, subsidies are given to routes with quite heavy traffic where the potential for ordinary commercial services could have been offered. In other subsidy programs, air services' role as lifeline transport can be questioned because there are modes of surface transport that probably can serve these lifeline needs. A clearer set of criteria for remoteness and lifeline services could perhaps be developed. The allocative efficiency of the services should be focused, i.e. that the level of service are aligned with market needs and regional policy objectives. There should also be a coordinated approach to the funding of services to remote regions across relevant transport modes.
Keywords: 330